2019
DOI: 10.1186/s13293-019-0249-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association of metabolic syndrome with low back pain among middle-aged Japanese adults: a large-scale cross-sectional study

Abstract: Background Although some recent studies have indicated an association between metabolic syndrome (MetS) and musculoskeletal disease, little is known about the association of MetS with low back pain (LBP). The present study aimed to investigate sex differences in the association of MetS and the clustering of MetS components with LBP among middle-aged Japanese individuals. Methods Study subjects were 45,192 adults (30,695 men, 14,497 women) aged 40–64 years who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The association of metabolic syndrome with low back pain has greater prevalence in women than in men [61] and in our study, female Db/Db mice on WD had the most substantial effects on vertebral bone structure and IVDs. A limitation of this study is that we did not assess the underlying mechanisms that might be responsible for these observed sex-effects.…”
Section: Plos Onesupporting
confidence: 51%
“…The association of metabolic syndrome with low back pain has greater prevalence in women than in men [61] and in our study, female Db/Db mice on WD had the most substantial effects on vertebral bone structure and IVDs. A limitation of this study is that we did not assess the underlying mechanisms that might be responsible for these observed sex-effects.…”
Section: Plos Onesupporting
confidence: 51%
“…We previously revealed the relationship of metabolic syndrome with LBP among middle-aged Japanese adults. 30 However, individual components of metabolic syndrome are significantly affected by various lifestyles. In the present study, we investigated the association between the clustering of multiple unhealthy lifestyle behaviors and LBP among all adults using a large-scale health checkup data in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Female Db/Db mice on WD had the most substantial effects on vertebral bone structure and IVDs. The association of metabolic syndrome with low back pain has greater prevalence in women than in men [46]. Sex dependent effects of leptin receptor deficiency were also suggested in a recent study by McCabe et al [47] who demonstrated that alterations of specific leptin receptor sites contributed to sex-dependent bone responses to leptin, which could be particularly relevant during juvenile obesity, where loss of leptin signaling could diminish bone development and growth [47].…”
Section: Discussionmentioning
confidence: 99%